2006
DOI: 10.1074/jbc.m601103200
|View full text |Cite
|
Sign up to set email alerts
|

Human Macrophage Migration Inhibitory Factor

Abstract: Macrophage migration inhibitory factor (MIF) is a pro-inflammatory mediator with the ability to induce various immunomodulatory responses and override glucocorticoid-driven immunosuppression. Some of these functions have been linked to the unusual enzymatic properties of the protein, namely tautomerase and oxidoreductase activities. However, there are conflicting reports regarding the functional role of these enzymatic properties in normal physiological homeostasis and disease progression. Therefore, we have p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
70
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 50 publications
3
70
0
2
Order By: Relevance
“…Macrophages incubated with endotoxin-free EhMIF only did not show any significant increase in TNF-␣ secretion (Fig. 3C), in agreement with a previous study done with mammalian MIF (10).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Macrophages incubated with endotoxin-free EhMIF only did not show any significant increase in TNF-␣ secretion (Fig. 3C), in agreement with a previous study done with mammalian MIF (10).…”
Section: Resultssupporting
confidence: 92%
“…Proinflammatory functions include the following: (i) MIF induces the secretion of inflammatory mediators, such as interleukin-6 (IL-6); (ii) MIF enhances TNF-␣ production by lipopolysaccharide (LPS)-stimulated immune cells; and (iii) MIF can counterregulate the anti-inflammatory activities of glucocorticoids (9)(10)(11)(12)(13)(14)(15)(16)(17). Many of the inflammatory effects of MIF are initiated via direct binding to its cell surface receptor, CD74 (18).…”
mentioning
confidence: 99%
“…Although the production of cytokines in response to MIF stimulation alone is controversial, the production of IL-8 by MIF stimulation of peripheral blood monocytes has been confirmed in multiple contexts (46,69). Human peripheral blood monocytes purified by adherence were plated at a density of ϳ2 ϫ 10 5 cells/ well in a 96-well plate.…”
Section: Methodsmentioning
confidence: 99%
“…Although these compounds hold great potential for clinical application, preclinical studies of MIF inhibitors have proven problematic, in large part due to a lack of a unified approach to developing bioassays for MIF activity. Although many candidate assays are employed, including cytokine production (46), signal transduction through the ERK pathway (6), proliferation and apoptosis studies (5,47), and chemotaxis experiments (4), these assays do not always produce robust results and are easily confounded by factors such as contaminating endotoxin in recombinant protein preparations.…”
Section: Macrophage Migration Inhibitory Factor (Mif)mentioning
confidence: 99%
“…Currently, the exact role of MIF in the regulation of the immune response is a subject of controversy. Numerous studies have shown that MIF activates or promotes the expression of tumor necrosis factor ␣ (TNF␣), interleukin-1 (IL-1), IL-2, IL-6, IL-8, and IL-12 from a variety of cell types, including macrophages and T cells (1)(2)(3)(4)(5)(6); other studies have failed to establish a cytokine or cytokine-inducing role of MIF (7)(8)(9)(10). However, MIF is capable of overriding the antiinflammatory actions of glucocorticoids, thus impairing glucocorticoid action (1,2,11).…”
mentioning
confidence: 99%